Controls over Body: How Politics Operates the Body in Vampire Academy Universe - Kustantinah, Indri; Ekasiswanto, Rudi; Thakur, Bikas Khumar (Universitas PGRI Semarang, 2026)
The concept of body politics underpins the rigid, oppressive class system in Richelle Mead’s Vampire Academy (VA) series, shaping how power is distributed and maintained across social groups. This study examines how power is enacted on individual bodies through mechanisms of regulation, control, and normalization that extend beyond formal authority. Drawing on the theoretical framework of Scheper-Hughes and Lock, particularly their notion of the body as a political and social reality, this research situates the body as a key site where ideology, morality, and power converge. Within this framework, social norms are shown to exert a disciplinary force that often surpasses the effectiveness of legal or institutional governance. Using qualitative textual analysis, the study examines narrative events, character interactions, and emotional responses within the Vampire Academy series, focusing on the lived bodily experiences of Moroi, Dhampir, and Humans. Special attention is given to how emotional regulation, physical discipline, and moral expectations are unevenly imposed across these groups. The analysis reveals that social stability in the VA universe is sustained by the interplay of religious morality and hierarchical class structures. Moral control manifests through the internalization of Christian-influenced ethical values, particularly those related to purity, sacrifice, and duty, which are reinforced through emotions such as guilt, fear, and obligation. At the same time, the class system dictates acceptable physical behaviour and bodily practices, especially in the militarization and instrumentalization of Dhampir bodies and the privileged protection of Moroi bodies. These dynamics demonstrate that power in the VA series functions most effectively not through overt violence alone, but through the internalization of norms that discipline both body and mind. Ultimately, the study argues that body politics in Vampire Academy serve as a critical mechanism for maintaining the existing social order by transforming domination into a normalized and emotionally accepted condition.